Per un “Atlante della documentazione comunale”. Presentazione del progetto on line - De Angelis, Gianmarco (Scrineum, 2013)
The paper gives a short presentation of the Web-site named Atlante della documentazione comunale (secoli XII-XIV), explaining its conditions (both theoretical and operational), contents and purposes.